Fallen angels sing - Torres, Omar, 1945- (Arte Publico Press, 2017)
To escape the wrath of a deceived husband, Miguel Saavedra abandons Miami's uprooted younger Cubans for New York, where he is caught in a web of plots spun by pro- and anti-Castro agents and lost in a journey that smears the line between fiction and reality.